Penguatan Kapasitas Komunikasi Digital Komunitas Mat Peci dalam Mendukung Pelestarian Sungai Ciliwung Berbasis SDGs - Wina Puspita Sari; Afina Ruqayyah; Rico Fernando Siregar; Adrian Maulana Malik Ibrahim; Arrumaisha Ghaida Puspitasari; Javier Rafi Putra Sidharto; Najla Faiza Ahmad (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2026)
This community service activity is motivated by the importance of Strengthening digital communication capacity within environmental communities to support the sustainability of community-based environmental conservation movements. The MAT PECI Community (Indonesian Community for Ciliwung Care) as an active partner in conservation and education along the Ciliwung River still faces limitations in managing digital organizational communication, particularly in documentation, publication, and social media optimization aspects. This activity aims to enhance the capacity of community members in utilizing digital media as a means of communication, education, and environmental advocacy. The method used is Participatory Action Research with a participatory approach that involves the community actively from problem identification, planning, implementation, to evaluation. The program includes digital communication training, mentoring in social media content creation, basic photography and videography training, and the development of community digital publication strategies. The results show an increase in members’ understanding and skills in using social media, behavioral changes toward more structured documentation, greater awareness of the importance of digital communication, and the formation of a more directed organizational communication system. The findings indicate that strengthening community-based digital communication is effective in social empowerment and supports the sustainability of environmental conservation movements.